Review paperSeborrhoeic-like dermatitis - Błaszkowski, Marcin; Kaczorowska, Anna; Staszek, Dariusz; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Seborrhoeic dermatitis (SD) is a frequent skin disease, which affects 5% of the human population. It is persistent and recurrent and the skin lesions occur on exposed skin areas, thus diminishing the quality of life of affected individuals. The aetiology of the disease is unknown and among possible triggering factors are seborrhoea, Malassezia colonization, alterations in the immunological response, mainly the cellular one, and disturbances in the skin anatomy or barrier function. In differential diagnosis, one should consider seborrhoeic psoriasis, seborrhoeic eczema and seborrhoeic pemphigus. In recent years, in the context of aetiopathology, course and therapy of SD, some authors have reported a nosological entity which is very much alike, but with somewhat different symptoms, different location, different therapy response and even a slightly different histopathological picture. These differences have led to the proposal of a new term: seborrhoeic-like dermatitis. In the paper some of the literature reports have been reviewed.